Volunteer farmer trainer approach in Eastern Africa - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Stage 4 - approach adopted throughout East Africa. An impact evaluation of a VFT training program led by ICRAF in Uganda showed that the program improved farmers’ knowledge of improved dairy farming practices as well as dairy productivity and revenues.